Modeling the process of removal aimed at cut traces on semiconductor wafers by using the method of contactless chemical-and-dynamical polishing - Pashchenko, G.A.; Kravetskyi, M.Yu.; Fomin, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Used in this work is the stationary model of the process of chemical-anddynamical polishing (CDP) the substrates in the case of balance between diffusion, convective and chemical fluxes. Obtained has been an analytical expression relating the surface shape in processed material with physical parameters of processes taking place under CDP. Calculations performed by the authors enabled to find technological regimes of processing that provides total removal of linear morphological defects from the surface of substrates after cutting. Comparison of experimental profilograms taken from the processed surfaces with theoretical dependences showed their satisfactory agreement.